Patrimonio arqueológico como factor de desarrollo turístico en la parroquia urbana Picoazá: caso parque arqueológico cerros hojas jaboncillo - Zambrano Loor, Wendy Stefanía (2019)
The objective of this research was to identify strategies that allow the development of tourism in the Picoazá urban parish through the revaluation of the archaeological heritage. It was an exploratory mixed investigation in which four phases were developed, the first consisted of an analysis of the community's linkage with tourism, with a general study of the main characteristics of Picoazá and the Cerros Hojas Jaboncillo Archaeological Park, the actors involved and current legislation through documentary search, interviews, surveys, stakeholder mapping and participatory workshops. In the second phase the tourism market was studied through surveys, SPSS, factorial, cluster and multivariable analysis to know consumption statistics, motivations and identify customer profiles, and evaluate potential and improvements of products and services. In the third phase, a strategic analysis of archaeological tourism in the territory was made to identify strengths, weaknesses, opportunities and threats with the SWOT matrix. In the fourth phase, tourism linkage and potentialization strategies were identified through the determination of strategic objectives, identification of actors and their functions, lines of action and compliance indicators with the application of the matrix of objectives and strategies. Among the main results highlighted the tourist-archaeological characteristics that Picoazá has and the social problems based on the inadequate articulation between the community and the actors involved, generating discontent in the inhabitants and lack of empowerment with its cultural wealth, it was identified that there is a tourism cultural motivated by archeology and another family motivated by visiting friends and family. In the strategic analysis, it is mainly proposed to promote local leadership and institutional leadership. Finally, strategies include social cohesion, culture and participation, urban adaptation and implementation of facilities and tourism promotion.